The Effect of Financial Performance and Capital Structure on Company Value: An Analysis of Transportation and Logistics - Meidawati, Neni; Saleh, Anjani Maula Zuhdi; Nustini, Yuni (Proceeding International Conference on Accounting and Finance, 2026)
This study aims to examine the influence of financial performance and capital structure on the value of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. Financial performance is measured using profitability ratios, while capital structure is assessed through the debt-to-equity ratio, and firm value is measured using market value indicators. The sample was determined using a purposive sampling method, with secondary data obtained from company financial reports that met the established criteria. Data were analyzed using multiple linear regression to evaluate the effect of financial performance and capital structure on firm value. The results show that financial performance has no significant effect on firm value, whereas capital structure has a positive effect. These findings provide important implications for company management and investors in making strategic decisions regarding capital structure to enhance firm value.